Representation of Animal Motifs in Indian Art Traditions - Chakraborty, Debasish (Recent Research Advances in Arts and Social Studies Vol. 6, 2024)
The spiritual manifestation of animal motifs in all the major works that is observed, showcased the inevitability for two most important animals - Elephant and Lion, whose appearance is unescapable in order to understand the narrative contents in the development of Indian Art. The relation between human and animals and its association in our daily activity is unavoidable. From its representation as a visual element in calendar art to the logo design for a brand, animals are the most viewed object in literary and art works. They play a very important role in understating the ecological efficacies to create an organised equilibrium in the nature. In Indian mythology, the practice of using animals as visual representations has a long history. Characters like Hanuman, the Monkey God, are one example of how this enhances the sacred scriptures of Hindu beliefs with tales of deeper wisdom and morals. A sense of reverence for animals is infused into our art and culture through the projection of animal images, which has been the pinnacle of Indian art heritage from antiquity to the present. The paper explores the presence of animals as visual motifs in the chronological development of Indian art in understanding the role of animals played in the story telling approaches.